A Comparative Evaluation of Intrathecal 0.75% Hyperbaric Ropivacaine versus Intrathecal 0.5% Hyperbaric Bupivacaine for Elective Infraumbilical Surgeries - Dr. Roshni Paryani; Dr Alpa Sonawane; Dr Chandini R Daniel; Dr. Dinesh Kumar Sahu; Dr Atul Sharma, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: With the current emphasis on ambulatory surgeries, bupivacaine has limited usefulness. Ropivacaine has low lipid solubility and is less cardiotoxic and neurotoxic than bupivacaine. It is gaining popularity because of its recovery profile. Hence, we designed a study to compare the clinical efficacy of 3 mL of 0.75% hyperbaric ropivacaine versus 3 mL of 0.5% hyperbaric bupivacaine under spinal anaesthesia for elective infraumbilical surgeries. Aim: To compare the clinical efficacy of 3ml of 0.75% hyperbaric ropivacaine versus 3ml of 0.5% hyperbaric bupivacaine under spinal anaesthesia for elective infraumbilical surgeries. Material and Methods: After approval from the institutional Ethics Committee, 80 adults aged 18-70 years with ASA I and II grades who presented for elective infraumbilical surgeries under spinal anaesthesia and fulfilled the inclusion criteria were enrolled in this study. According to the randomisation, patients were divided into two groups of 40 each. They received an intrathecal injection of 0.75% hyperbaric ropivacaine (3 mL) in group A or 0.5% hyperbaric bupivacaine (3 mL) in group B. Vital signs were monitored, and block parameters were observed. Adverse events and the time to first micturition were noted. The data were presented as means with standard deviations and frequencies with percentages. The data were analysed using statistical software SPSS version 21. Result: Ropivacaine produced a slower mean onset of sensory block (11.55 vs 6.63 mins; p<0.01), and the mean total duration of sensory block was significantly shorter (234.75 vs 288.75 mins; p<0.01) as compared to bupivacaine. Patients in the bupivacaine group achieved a higher level of peak sensory block (p-0.048). The onset of motor block was significantly slower (10.45 vs 6.3 minutes; p < 0.01) and the duration was shorter (206.25 vs 258.75 minutes; p < 0.01) in the ropivacaine group. Post the induction, SBP and MAP were significantly lower in the bupivacaine group as compared to ropivacaine from the 4th min onwards till the 15th min (p<0.01), and DBP was substantially lower in the bupivacaine group as compared to ropivacaine from the 2nd min onwards till the 15th min (p<0.01). The time to first micturition was significantly faster with ropivacaine compared to bupivacaine (357.87 vs 403.97 minutes; p < 0.01). Conclusion: The study concludes that 0.75% hyperbaric ropivacaine, despite its slower onset of action, can serve as a good alternative to 0.5% hyperbaric bupivacaine for spinal anaesthesia in elective infraumbilical surgeries of short to intermediate duration, offering the added advantages of earlier recovery and more stable hemodynamics.